Has Kelantan grown faster than other states in Malaysia? A panel data analysis - Muzafar Shah Habibullah,; Peter Smith,; Dayang Affizah , A.M (Penerbit Universiti Kebangsaan Malaysia, 2011)
Kelantan has been the poorest state in Malaysia for the past five deacades. Despite the vatious Malaysian development plants for the past several decades, regional disparity between states remains in Malaysia. Thus,the objectives of the present paper is to address the question whether Kelantan has been narrowing their income gap with other states in Malaysia. Using annual data for the period 1961 to 2003, our panel unit root test result suggest that (1) Kelantan converges towards Kedah, Negeri Sembilan, Perak, Pahang, Perlis and Selangor ; (2)Kelantan is caching-up to Johor, Melaka, Penang, Sabah, Terengganu and Wilayah pesekutuan; and (3)Kelantan show divergence with Sarawak.In this respect, the government has an important role to play in enhancing growth by continuously providing stable economic environment for investment and other productive economic activities. This will ensure full convergence can take place in the future.